The Tough Realities Small NGOs Face When Evaluating Their Efforts: Observations from Guatemala and Mexico - Swindle, Jeffrey (Consilience, 2011)
Evaluation improves the quality of work completed by international non-governmental organizations (NGOs) to fight poverty and develop communities (Liebenthal et al. 2004). Even so, many NGOs do not conduct evaluations (Ferguson 1990). To the extent that NGOs evaluate their efforts, the evaluation results often do not affect the planning of future projects, making evaluation a static event instead of a learning process (Mebrahtu 2002). Thus, the relevant problem is how to make evaluation more useful. Mulwa (2008) argues that participatory evaluation bridges the disconnect between evaluation results and future development projects. Based on my experience, I emphasize the need for development evaluation to be practical; evaluations informed by all stakeholders create a climate of learning. Evaluations lead to improved development when the evaluation responsibilities and measurements are shared between all parties involved.